(untitled) (Ameghiniana, 2013)
Distribution of trace fossil assemblages from the slope deposits of the Kotick Point Formation (Cretaceous, James Ross lsland , Antarctica) seems to be chiefly controlled by degree of oxygenation. Feeding structures of opportunistic deposit feeders are dominant in the coarse deposits of the foot slope wedge. Trace fossils are scarce in sandy lobe deposits. In mudstones of interchannel origin, concretions are commonly non-bioturbated evidencing prevalent deposition under anaerobic conditions. More rarely, concretions containing a low-diversity assemblage of deposit feeders feeding structures (Zoophycos-Chondrites-Planolites) may reflect anaerobic interstitial waters, but aerobic to dysaerobic bottom waters. Turbidite sandstones of the slope show a trace fossil assemblage dominated by grazing trails (Pascichnia) of deposit feeders (e.g. Scalarituba, Phycosiphon). The assernblage characterizes aerobic bottom water and dysaerobic interstitial water. Turbidite beds with lag deposits host a trace fossil assemblage dominated by dwelling structures (Domichnia) of suspension feeders (Thalassinoides-Skolithos-Palaeophycus) and feeding structures of deposit feeders (Zoophycos-Chondrites-Planolites-Teichichnus). Deepest ichnoguilds within an anaerobic to dysaerobic sediment are characterized by Fodinichnia, whereas the shallowest ichnoguilds in aerobic conditions are dominated by Domichnia. In these proximal areas, intense currents provide oxygen and suspended food, allowing the development of suspension feeders. An ichnoassemblage dominated by dwelling structures of suspension feeders is present in the channel, terrace and sandy plain deposits of the Whisky Bay Formation. Aerobic conditions predominate in these arcas of a braided submarine channel complex. Ichnologic and sedimentologic data indicate that an oxygen-controlled model is useful to explain ichnofaunal variations in a slope setting. Turbidity currents played a major role in the environmental dynamics, supplying oxygen to an otherwise anaerobic slope.